Induction of Regulatory T Cells by Intravenous Immunoglobulin: A Bridge between Adaptive and Innate Immunity - Kaufman, Gabriel N.; Massoud, Amir H.; Dembele, Marieme; Yona, Madelaine; Piccirillo, Ciriaco A.; Mazer, Bruce D. (Frontiers in Immunology, 2015)
IVIg is a polyclonal IgG preparation with potent immunomodulatory properties. The mode of action of IVIg has been investigated in multiple disease states, with various mechanisms described to account for its benefits. Recent data indicates that IVIg increases both the number and suppressive capacity of regulatory T cells, a subpopulation of T cells that are essential for immune homeostasis. IVIg alters dendritic cell function, cytokine and chemokine networks, and T lymphocytes, leading to development of regulatory T cells. The ability of IVIg to influence Treg induction has been shown both in animal models and in human diseases. In this review, we discuss data on the potential mechanisms contributing to the interaction between IVIg and the regulatory T cell compartment.